Pengembangan Kreativitas Siswa Melalui Pengajaran Seni Rupa di TK Pertiwi dan TK ABC Preschool Padang Panjang - Asnaini Asnaini; Dela Suraini; Lina Nabilah; Sarimia Afriza; Suci Fatmawati; Syifa Uzzahra; Ayu Citra Dewi M. Pd (Institut Nalanda, 2025)
Children's fine arts education through drawing is useful for knowing the child's development to what extent children are familiar with the fine art of drawing. The aim of this research is to analyze and describe the implementation of fine art drawing learning for early childhood children. This research method uses a qualitative approach, with data collection techniques used being observation, interviews and documentation. The results of the research show that drawing activities can be an alternative tool for approaching the conception of fine arts education in early childhood, because through drawing teachers can also increase children's understanding of fine arts broadly and teachers can also increase children's creativity and imagination and become a forum for children. child. children to express creative ideas. Drawing activities can be a tool for teachers to create an interesting and fun learning atmosphere for children, so that children don't get bored while learning and learning doesn't go monotonous.